A Phonological Description of the Local Dialect of Dobovec pri Rogatcu (SLA Data Point 339) - Jakop, Tjaša (Jezikoslovni zapiski, 2024)
This article presents the basic phonetic and accentual characteristics of the local dialect of Dobovec pri Rogatcu, which is part of the Srednještajersko (Middle Styrian) dialect in the Styrian dialect group. It describes the general phonological, phonetic, and accentual features of this dialect. The phonological description of this local dialect is based on dialect material collected by Jurij Rojs for the Slovenian Linguistic Atlas (SLA) in 1966. The material was written in the old Ramovš’s transcription and has been transcribed into the modern Slovenian phonetic transcription for the purpose of this article.